Hepatic Steatosis Aggravates Vascular Calcification via Extracellular Vesicle‐Mediated Osteochondrogenic Switch of Vascular Smooth Muscle Cells - Zhao‐Lin Zeng; Zhi‐Bo Zhao; Qing Yuan; Shi‐Qi Yang; Zhen‐Xing Wang; Zuo Wang; Shi‐Yu Zeng; An‐Qi Li; Qian Chen; Guo‐Qiang Zhu; Xin‐Hua Xiao; Guang‐Hua Luo; et al. (Advanced Science)
Abstract The global incidence of metabolic dysfunction‐associated fatty liver disease (MAFLD) has risen sharply. This condition is strongly associated with the risk of cardiovascular disease (CVD), but how MAFLD affects the development and progression of CVD, particularly concerning vascular calcification, remains unclear. Herein, extracellular vesicles (EVs) are identified from steatotic hepatocytes as a trigger that accelerated the progression of both vascular intimal and medial calcification. Steatotic hepatocytes are found to release more EVs, which are able to reach the vascular tissue, be taken up by vascular smooth muscle cells (VSMCs), and promote their osteogenic differentiation. Within these toxic vesicles, a protein cargo is identified called lectin galactoside‐binding soluble 3 binding protein (Lgals3bp) that acted as a potent inducer of osteochondrogenic transformation in VSMCs. Both the inhibition of EV release and the liver‐specific knockdown of Lgals3bp profoundly attenuated vascular calcification. This work partially explains the reason for the high incidence of vascular calcification in MAFLD and unveils a novel mechanism that may be used to prevent or treat cardiovascular complications in patients with MAFLD.